Frequency of UTI in patients taking Empagliflozin versus Dapagliflozin in patients with type 2 diabetes Mellitus - Arshad, Hatib; Sheikh, Ghulam Abbas (Indus Journal of Bioscience Research, 2025)
Introduction: Individuals with diabetes are more likely than those without the disease to get a UTI. Determining the prevalence of genitourinary infections in individuals with type 2 diabetes receiving treatment with two SGLT-2 inhibitors (dapagliflozin and empagliflozin) was the aim of the current investigation. Future recommendations for medications that lessen UTIs will be made in order to lower morbidity in these people. Study Design: Randomized Controlled Trail. Settings: Department of Medicine, Aziz Fatima Hospital, Faisalabad. Materials & Methods: There were 90 (45 in each group) type 2 diabetes individuals of either gender who were older than 18 and using SGLT-2 inhibitors as monotherapy or combination therapy. Participants were excluded if they had gestational diabetes, had a UTI within the last three months, were pregnant or nursing. Those in group B received 25 mg of empagliflozin for three months, while those in group A received 10 mg of dapagliflozin. The patients were told to collect their urine midstream in a sterile urine bottle for analysis. Three months later, the results were documented in terms of UTI. Results: Patients in groups A and B had mean ages of 39.51 ± 10.22 and 40.31 ± 8.36 years, respectively. The majority of the 47 patients (52.22%) were in the 19–40 age range. With a male to female ratio of 1:1.4, 37 (41.11%) of the 90 patients were men and 53 (58.89%) were women. Three patients (6.67%) in Group A (dapagliflozin group) and fifteen (33.33%) in Group B (empagliflozin group) had UTIs on average (p-value = 0.0016). Conclusion: According to this study, people with type 2 diabetes mellitus who take empagliflozin have a higher incidence of UTIs than those who take dapagliflozin.